Differential Cellular Expression of Galectin-1 and Galectin-3 After Intracerebral Hemorrhage - Bonsack, Frederick; Sukumari-Ramesh, Sangeetha (Frontiers in Cellular Neuroscience, 2019)
Abstract Intracerebral Hemorrhage (ICH) is a devastating sub-type of stroke with no proven treatment. Given the emerging role of Galectin-1 and Galectin-3 in neuroimmune responses, the objective of the current manuscript is to elucidate hemorrhagic-injury induced modulation and cellular expression of Galectin-1 and Galectin-3 in the brain in a pre-clinical model of ICH. To address this, ICH was induced in male CD1 mice by collagenase injection method. Western blotting as well as Immunofluorescence staining was performed to characterize the temporal expression pattern as well as cellular localization of Galectin-1 and Galectin-3 after ICH. Further, genetic studies were conducted to assess the functional role of Galectin-1 and Galectin-3 in inflammatory response employing a murine macrophage cell line, RAW. 264.7 cells. Galectin-1 and Galectin-3 exhibited very profound and increased expression from day 3 to day 7-post-injury, in the perihematomal brain region after ICH in comparison to Sham. Further, Galectin-1 expression was mostly observed in GFAP-positive astrocytes whereas Galectin-3 expression was observed mostly in Iba1-positive microglia/macrophages as well as CD16/32 (M1 microglial/macrophage marker)-positive cells. Moreover, genetic studies revealed a negative regulatory role of both Galectin-1 and Galectin-3 in the release of a proinflammatory cytokine, IL-6 from RAW. 264.7 cells. Altogether, The present manuscript demonstrates for the first time, increased expression as well as cellular localization of Galectin-1 and Galectin-3 in the perihematomal brain regions after ICH. In addition, the manuscript raises the potential of Galectin-1 and Galectin-3 in modulating glial responses and thereby brain injury after ICH, warranting further investigation.